Study protocol of associated criteria used in investigating septic transfusion reactions (STRs): A scoping review about available evidence. - Dilaram Acharya; Antoine Lewin; Amaury Gaussen; Gilles Lambert; Christian Renaud; Karlitaj Nawej; Thomas G Poder (PLoS ONE)
Background and objective Assessment criteria for septic transfusion reactions (STRs) are variable around the world. A scoping review will be carried out to find out, explore and map existing literature on STRs associated criteria. Methods This scoping review will include indexed and grey literatures available in English or French language from January 1, 2000, to December 31, 2021. Literature search will be conducted using four electronic databases (i.e., MEDLINE via PubMed, Web of Science, Science Direct, and Embase via Ovid), and grey literatures accompanying the research questions and objectives. Based on the inclusion criteria, studies will be independently screened by two reviewers for title, abstract, and full text. Extracted data will be presented in tabular form followed by a narrative description of inputs corresponding to research objectives and questions.